Case report: Analysis of a gene variant and prenatal diagnosis in a family with megalencephalic leukoencephalopathy with subcortical cysts - Chen, Xi; Qu, Haibo; Yao, Qiang; Cai, Xiaotang; He, Tiantian; Zhang, Xuemei (Frontiers in Neurology, 2023)
Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare inherited cerebral white matter disorder in children. Pathogenic variations in the causative gene MLC1 are found in approximately 76% of patients and are inherited in an autosomal recessive manner. In this study, we identified an IVS2 + 1delG variant in MLC1 in the firstborn girl of a pregnant woman who has the clinical features of MLC, including macrocephaly, motor development delay, progressive functional deterioration, and myelinopathy, whereas no obvious subcortical cysts were observed by magnetic resonance imaging of the brain. The proband is homozygous for the IVS2 + 1delG mutation, which was inherited from the parents. This variant disrupts the donor splice site, causing an abnormal transcript that results in a premature termination codon and produces a truncated protein, which was confirmed to affect splicing by MLC1 cDNA analysis. This variant was also detected in family members, and a prenatal diagnosis for the fetus was undertaken. Eventually, the couple gave birth to an unaffected baby. Furthermore, we conducted a long-term follow-up of the proband’s clinical course. This report improves our understanding of the genetic and phenotypic characteristics of MLC and provides a new genetic basis for prenatal diagnosis and genetic counseling.